Avaliação probabilística da resistência à compressão axial de perfis de aço formados a frio - Bruno Torres Pichara Sily (2012)
The cold-formed steel profiles (CFP) have been used each time more in civil construction. Its increased use is due, mainly, to the design of structures ever more slender and the great variability of their cross sections available in the market. To this end, the CFP can be usedin different conditions of required strength in a structure, it may be mentioned the axial compression, which will be studied in this work.To calculate the compressive strength of the CFP, it should considerate the modes of local and global buckling, being possible the occurrence of some interaction between them. The local modes include the local and distortional buckling. For global modes there are the flexural, torsional and flexural-torsional buckling. However, the resistance of these profiles is not a deterministic value, having in fact a random nature. Therefore, it is important to collect information about the inherent and epistemic uncertainties related to the compressive strength of CFP. The inherentuncertainties are those whose variability can not be changed unless, in case of CFP, there is an interference in the process of manufacturing these. As such uncertainties can be mentioned those that are associated with the material and the geometrical dimensions of the profiles. The epistemic uncertainties are those related to the degree of knowledgeconcerning a given problem. Like examples of this latter, it can be pointed out the model error and the sampling error. Thus, this work aims to obtain, by Monte Carlo simulation, the probability distribution ofthe compressive strength of CFP to three distinct types of cross sections (U, stiffened U and stiffened S), taking into account these uncertainties of inherent and epistemic nature.